The Effect of an Instructional Program based on the Blended Learning Strategy in Enhancing English Pragmatic Competences among the Secondary Stage Students - Dr. Homaid Abdulhameed Al-Mansouri (Journal of Educational and Human Sciences, 2024)
The present study aimed at investigating the effect of an instructional program based on the blended learning strategy in enhancing English pragmatic competences among the secondary stage students in Saudi Arabia Kingdom. To fulfil the purpose of the study, the quasi-experimental design was adopted (pretest - post-test). The participants, totalling (56), were randomly selected form the second-year students in a public secondary school in Taif in Saudi Arabia. They were assigned into two groups: An experimental group (N= 28) that studied via an instructional program based on the blended learning strategy and a control one (N=28) that studied via the traditional method. The instrument consisted of a pragmatic competences tests to assess both discourse and functional competences. The results of the study revealed that: There was a statistically significant difference (α ≤ 0.05) between the mean scores of the control group and the experimental group in the post-administration of the pragmatic competence test, in favor of the experimental group. The study recommended developing Training English language teachers on how to exploit technology to boost collaboration among students and integrate the pragmatic competence teaching in their courses. In addition, the researcher suggested conducting further studies into blended learning strategy and pragmatic competences in English as a foreign language.